Analysis of The Influence of Employee Stock Ownership Program (ESOP) Application of Company Financial Performance - Fitri Handayani; Yurniwati Yurniwati (Universitas Batanghari Jambi, 2020)
This study aims to examine the effect of implementing the Employee Stock Ownership Program (ESOP) on the company's financial performance. and differences in the company's financial performance when issuing ESOPs and not issuing ESOPs. The implementation of ESOP is proxied by the proportion of ESOP and the price of execution, the company's financial performance is proxied by ROE, NPM, and OPM. The research was conducted on companies listed on the IDX and have adopted the ESOP in 2012 to 2016. The sampling method uses purposive sampling. To test the effect of applying ESOP on performance. The results of this study indicate that the number of ESOP Provisions given has no effect on ROE, NPM, and OPM. ESOP execution prices affect the value of ROE and NPM but do not affect the value of OPM. There is no difference in the value of ROE, NPM, and OPM when the company issues ESOP and does not issue ESOP.